REPORTE DE CASO: SALMONELOSIS EN VACAS LECHERAS - Gauchat, L (Universidad Nacional del Litoral, 2022)
Salmonellosis is an infectious disease associated with enteritis, septicemia, and reproductive losses in adult dairy cows. Transmission usually occurs via the fecal-oral route and Salmonella dublin is the most common serotype isolated in bovines. Although several studies have examined the prevalence of fecal Salmonella shedding on dairy farms, there is very little information available regarding the occurrence of clinical disease associated with Salmonella infections in cattle. We report herein an outbreak of Salmonellosis in dairy cows from Santa Fe, Argentina. The diagnosis was confirmed by gross and microscopic changes combined with aerobic culture. Animals showed a clinical history of diarrhea, fever, anorexia, dehydration and death. The gross and histologic lesions were a necrotizing hepatitis, lymphadenitis and splenitis with characteristic paratyphoid nodules, fibrinous cholecystitis and a necrotizing enteritis. The possible predisposing factors in these cases were mycotoxins present in the feed and the presence of backyard poultry and pigs in the farm.